Detection of Ethyl Parathion Using Microcantilever Biosensor - Xue, Changguo; Nan, Tiegui; Wu, Shangquan; Cao, Zhen; Zhang, Qingchuan; Wang, Baomin (Asian Journal of Chemistry, 2012)
A microcantilever biosensor has been developed for label-free detection of ethyl parathion. Through self-assembled monolayer (SAM) method, anti ethyl parathion antibody was immobilized on the gold surface of the microcantilever for the measurement of ethyl parathion. The deflection of the microcantilever corresponding to different ethyl parathion concentration was real time monitored by optical lever technique. The experimental results of non-competitive enzyme-linked immunosorbent assay (ELISA) indicate that anti ethyl parathion antibody on the gold surface can keep the activity. Deflection of microcantilever is linear to ethyl parathion concentration from 500-2000 ng/mL. The limit of detection is 500 ng/mL.